Culture's Impact on the Importance of Fairness in Interorganizational Relationships. Issue 4 (December 2013) - Lund, Donald J.; Scheer, Lisa K.; Kozlenkova, Irina V.
Research on interorganizational relationships is predicated on the idea that fairness is always important. The authors question this assumption because most fairness research has been conducted in Western countries, and mixed empirical support draws into question how important fairness actually is. Drawing on Hofstede's cultural dimensions framework, the authors examine culture as an antecedent to the importance of outcome fairness (OF) and procedural fairness (PF) in retailers' assessments of their relationships with suppliers. The authors also propose that cultural exposure moderates the impact of culture on fairness importance. Using responses from retailers in ten countries analyzed with hierarchical linear modeling, the authors find that uncertainty avoidance enhances the importance of OF and PF, power distance marginally decreases the importance of PF, and long-term orientation increases the importance of both OF and PF. Cultural exposure also positively moderates the impact of uncertainty avoidance and masculinity on both fairness types. The pattern of effects is robust when compared with two alternative models. This study offers a first step in understanding culture's impact on when fairness is more or less important.